Évaluation de la qualité des eaux albiennes de la région de l'oued M'zab à l'aide de l'indice de qualité des eaux - Tahar, Ikram; Sendjal, Chourouk (Université de Ghardaia, 2025)
Les ressources d’eau d’oued M’Zab sont des eaux souterraines non renouvelables à cause du climat sec de la région. Une compagnie d'échantillons de 18 puits de différentes points de l’amont vers l’aval du la vallée d’oued M’Zab. Les analyses physico-chimiques ont été faites en laboratoire (ADE), et l’Indice de Qualité de l’Eau (IQE) a été calculé à l’aide d’un programme Excel basé sur les équations mathématiques internationales et des normes algériennes. Les résultats montrent que l’eau de la région est globalement de bonne qualité avec un IQE moyen de 48,06, 62 % des puits en eaux de bonne qualité et 38 % en eau de mauvaise qualité. Les bonnes qualités d’eau se trouvent principalement à Daïa et Ghardaïa, tandis que les mauvaises qualités sont observées à l’aval, surtout à El’ Atteuf , zone agricole où se trouve les eaux stagnantes et l’activité agricole. Tous les échantillons dépassent les normes algériennes pour les sulfates et la dureté tandis que les éléments de pollution sont négligeables à cause de la forte minéralisation.
Keywords: Irrigation -- Mzab; Puits -- Mzab

Variation spatio-temporelle et statistique de la qualité des eaux souterraines de la ville de Ghardaïa - Ben Sedira, Abdelkader (Université de Ghardaia, 2025)
Keywords: Puits -- Mzab

Traditional Irrigation installations in the M’zab Valley - Zaaba, Omar (Herodotus' Journal of the Human and Social Sciences, 2025)
Keywords: Agriculture -- Mzab; Irrigation -- Mzab; Puits -- Mzab

تيرسين نات-مليشت= آبار آت مليشت: إرث الأجداد وقف للأحفاذ - باعمارة, سليمان بن أحمد (مؤسسة منارة الإيمان, 2024)
Keywords: Monuments -- Mzab; Puits -- Mzab

The Social Practices And Their Architectural Reflections On The Dwelling In The M'zab Valley Traditional - Zaaba, Omar; Barkat, Omar (Journal of Namibian Studies : History Politics Culture, 2024)
The traditional architecture in the M'zab Valley was a real response to the needs of the natural community and a direct reflection of its lifestyle, nature of activities, environmental requirements, individual and collective life practices within the intellectual system and its natural framework. Therefore, we do not find any part in this architecture that does not serve a specific function or symbolize a certain goal, considering that all material production in this society is a homogeneous and harmonious expression between needs, aspirations, goals, religious values, organizations and interactive social relationships with nature and climatic factors. Thus, architectural production in general and traditional housing in M'zab specifically testify to all these values and ideas manifested in their patterns, plans, units and architectural elements, It was necessary to study the impact of these social organizations and practices on the traditional dwelling in M'zab, considering it as a fundamental urban unit in shaping its palaces and a real product that reflects the values and ideas of this society. And since the dwelling is part of this human production, its relationship with social practice is a strong and organic relationship.
Keywords: Architecture -- Mzab; Irrigation -- Mzab; Puits -- Mzab

Hydrologie du Sahara algérien. Texte : extrait des documents relatifs à la mission de Laghouat, El-Goléa, Ouargla, Biskra (rapport hydrologique) - Rolland, Georges (Imprimerie nationale, 1894)
Keywords: Puits -- Mzab